2013
DOI: 10.1093/infdis/jit094
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Resolution of Genital Chlamydia trachomatis Infection in Women and Protection from Reinfection

Abstract: The natural history of chlamydia is variable and may include persisting asymptomatic infection, complications, or spontaneous resolution before treatment. Reinfection is common. We evaluated whether spontaneous resolution was associated with decreased reinfection in women returning for treatment of a positive chlamydia screening test. At enrollment, participants were tested for chlamydia, treated with azithromycin, and scheduled for a 6-month follow-up visit for repeat testing. Two hundred participants returne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(100 citation statements)
references
References 31 publications
6
94
0
Order By: Relevance
“…The potential clinical significance of spontaneous resolution is that patients who clear CT infection before treatment have a lower reinfection risk than those with persisting infection [5]. It has been suggested this may be because patients whose infections spontaneously resolve develop protective immunity, in contrast to those with persisting infection having "arrested" immunity if treated too early in their infection [6].…”
Section: Persisting Genital Chlamydia Trachomatis (Ct) Infection Can mentioning
confidence: 99%
“…The potential clinical significance of spontaneous resolution is that patients who clear CT infection before treatment have a lower reinfection risk than those with persisting infection [5]. It has been suggested this may be because patients whose infections spontaneously resolve develop protective immunity, in contrast to those with persisting infection having "arrested" immunity if treated too early in their infection [6].…”
Section: Persisting Genital Chlamydia Trachomatis (Ct) Infection Can mentioning
confidence: 99%
“…resolving infection before treatment) occurs in 5 approximately 11-44% of women in the interval between a positive Ct screening test and returning for treatment [10]. Although the mechanisms involved in natural clearance are poorly understood, one study reported that women who naturally cleared Ct infection were 4-fold less likely to be re-infected within 6 months, suggesting adaptive immunity (perhaps via IFN--mediated tryptophan depletion) may contribute to natural clearance and protective immunity [11]. The primary objective of our study was to determine whether tryptophan, indole, and IFN- concentrations were associated with natural clearance of Ct infection in humans.…”
Section: Animal Models Of Chlamydia Infection Have Demonstrated That mentioning
confidence: 99%
“…Adaptive immunity likely contributes to this process, evidenced by the association between natural clearance of Ct infection and reduced Ct reinfection rates [11]. IFN- is crucial for effective Ct clearance in animal models [2], and likely humans [3,4], by signaling tryptophan depletion, as shown in vitro [6].…”
mentioning
confidence: 99%
“…As koala chlamydial infection is widespread and often asymptomatic in free ranging animals, a prophylactic vaccine is of paramount importance. Recent studies showed that women with C. trachomatis infection without clinical disease, and treated with antibiotic, had a significant level of subsequent reinfections within a 1 year time period [83]. This clearly suggests that some individuals receiving antibiotic treatment did not develop protective immunity [84].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic disease is associated with cystic changes in the oviduct and ovarian bursae and in some cases thickening of the uterine wall. Prostatic abscess formation is the prominent pathological finding for male koalas [83,84]. Ocular infections result in inflammation, characterised by conjuctival hyperplasia and progressing to fibrosis.…”
Section: Pathological Lesionsmentioning
confidence: 99%